The Last Hindu Emperor : Prithviraj Chauhan and the Indian Past, 1200-2000 - Talbot, Cynthia (Cambridge University Press, 2016)
"This fascinating new study traces traditions and memories relating to the twelfth-century Indian ruler Prithviraj Chauhan, a Hindu king who was defeated and overthrown during the conquest of Northern India by Muslim armies from Afghanistan. Surveying a wealth of narratives that span more than 800 years, Cynthia Talbot explores the reasons why he is remembered, and by whom. In modern times, the Chauhan king has been referred to as 'the last Hindu emperor', because Muslim rule prevailed for centuries following his defeat. Despite being overthrown, however, his name and story have evolved over time into a historical symbol of India's martial valor. The Last Hindu Emperor sheds new light on the enduring importance of heroic histories in Indian culture and the extraordinary ability of historical memory to transform the hero of a clan into the hero of a community, and finally a nation"--